О структуре общего непрерывного решения систем линейных разностных уравнений с непрерывным аргументом - Пелюх, Г.П. (Видавничий дім "Академперіодика" НАН України, 2007)
We consider the structure of a set of continuous solutions of one class of systems of linear difference equations with continuous argument.